Managerial competencies and downward accountability of relief aid organisations in western Uganda - Aryatwijuka, Wilbroad; Kamukama, Nixon; Frederick, Nsambu Kijjambu; Rukundo, Aloysius (Journal of Strategic Management, 2020)
The Purpose: The paper presents the effect of managerial competencies on downward accountability of relief aid organisations in western Uganda. Methodology: This was a cross-sectional survey and correlational study. Stratified and simple random sampling techniques were employed and a questionnaire used to collect data from 105 out of 150 relief aid organisations operating in western Uganda. Data analysis was conducted using zero order correlation and hierarchical regression aided by SPSSv22. The unit of inquiry was the staff of the relief aid organisations involved in relief supplies. Findings: The results of the study showed that there is a significant positive relationship between managerial competencies and downward accountability. Unique contribution to practice and policy: This study will provide an understanding of the relationship between managerial competencies and downward accountability among relief aid organisations in western Uganda. For relief aid organisations in western Uganda to improve on downward accountability, they need to recruit staff with professional, social and personal competencies so as to ensure downward accountability. Research Limitation: The study did not examine the influence of other factors such as the operational environment and donor requirements, on downward accountability but solely concentrates on managerial competencies. Additionally, this was a cross sectional study yet relief operations change over and this could have yielded different findings. Originality/value: The current study focuses on the humanitarian downward accountability in the context of a developing country and more so in the downstream of the supply chain.
Its an article about managerial competance
Keywords: Managerial competencies; Accountability; Relief aid organisations